2012
DOI: 10.1016/j.peva.2010.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Spatial fairness in linear random-access networks

Abstract: Random-access networks may exhibit severe unfairness in throughput, in the sense that some nodes receive consistently higher throughput than others. Recent studies show that this unfairness is due to local differences in the neighborhood structure: nodes with fewer neighbors receive better access. We study the unfairness in saturated linear networks, and adapt the random-access CSMA protocol to remove the unfairness completely, by choosing the activation rates of nodes as a specific function of the number of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…We now repeat the same experiment, but instead of using equal rates we set the activation rate νi = α(1 + α) γ(i)−γ (1) , which guarantees fairness in low and heavy traffic as proven in Theorem 6 and fairness in all cases when C = 1 due to [18]. Figure 4 depicts the fairness index in a line network consisting of n = 40 links as a function of the parameter α.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We now repeat the same experiment, but instead of using equal rates we set the activation rate νi = α(1 + α) γ(i)−γ (1) , which guarantees fairness in low and heavy traffic as proven in Theorem 6 and fairness in all cases when C = 1 due to [18]. Figure 4 depicts the fairness index in a line network consisting of n = 40 links as a function of the parameter α.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The main result in [18] showed that in case of a single channel, i.e., C = 1, fairness can be achieved in a line network consisting of n links if νi = α(1 + α) γ(i)−γ (1) , for i = 1, . .…”
Section: Fairnessmentioning
confidence: 99%
“…The two main reasons are the irregularity in the network topology and protocol behaviors that lead to starvation for some nodes. There have been efforts towards improving fairness by tuning protocols, for example, adjusting carrier sense range [29] or using node specific access intensity [28], [30], [31].…”
Section: A Unfairness In Csma Networkmentioning
confidence: 99%
“…Unfairness in a large CSMA system caused by the unfair advantage of border nodes at high access rates was analyzed in [8]. To eliminate border effects, channel access rates which equalize throughputs are proposed for linear networks and 2 × N grids [9,10]. Determination of channel access rates which achieves target throughputs is investigated in [11].…”
Section: Related Workmentioning
confidence: 99%